Proteomic analysis of Lactobacillus pentosus for the identification of potential markers of adhesion and other probiotic features. (September 2018) - Pérez Montoro, Beatriz; Benomar, Nabil; Caballero Gómez, Natacha; Ennahar, Said; Horvatovich, Peter; Knapp, Charles W.; Alonso, Esther; Gálvez, Antonio; Abriouel, Hikmate
Abstract: We analyzed the adhesion capacity to mucus of 31 Lactobacillus pentosus strains isolated from naturally fermented Aloreña green table olives using an immobilized mucin model. On the basis of their adhesive capacity to mucin, three phenotypes were selected for cell-wall protein proteomic analysis to pinpoint proteins involved in the adhesion process: the highly adhesive L. pentosus CF1-43 N (73.49% of adhesion ability), the moderately adhesive L. pentosus CF1-37 N (49.56% of adhesion ability) and the poorly adhesive L. pentosus CF2-20P (32.79% of adhesion ability). The results revealed four moonlighting proteins over-produced in the highly adhesive L. pentosus CF1-43 N, which were under/not produced in the other two L. pentosus strains (CF1-37 N and CF2-20P). These proteins were involved in glycolytic pathway (phosphoglycerate mutase and glucosamine-6-phosphate deaminase), stress response (small heat shock protein) and transcription (transcription elongation factor GreA). Furthermore, the relative fold change in gene expression analysis showed significant up-regulation of the genes coding for these four moonlighting proteins in the highly adhesive L. pentosus CF1-43 N versus the poorly adhesive L. pentosus CF2-20P and also in response to mucin for 20 h which clearly indicate the significant role of these genes in the adhesion capacity of L. pentosus . Thus, these proteins could be used as biomarkers for mucus adhesion in L. pentosus . On the other hand, mucin exposure induced other probiotic effects in L. pentosus strains, enhancing their co-aggregation ability with pathogens and possible inactivation. Graphical abstract: Unlabelled Image Highlights: Proteomic data reveal adhesion mechanisms in Lactobacillus pentosus . Four moonlighting proteins were over-produced in the highly adhesive L. pentosus . PGM, GNPDA, GreA and small heat-shock protein as adhesion biomarkers in L. pentosus . pgm, nagB and greA genes were up-regulated in response to mucin. High co-aggregation ability of L. pentosus strains pre-exposed to mucin.